Nezamestnanosť a podpora uplatnenia absolventov na trhu práce - Husáková, Mária; Pechová, Michaela (Univerzita Pardubice, 2011)
On the development of unemployment in 2009, worked several factors that were associated with the global economic crisis. Big problem is the long term unemployment. The Slovak Republic in December 2010 recorded 48.44 percent of job seekers registered at employment office for more than one year. A big problem in the labor market are young people and its placement . Graduate experience as one of the active labor market measures assist the unemployed graduates in the age of 25 years.
Keywords: unemployment; young people; long term unemployment; graduate practice; active labor market measures